1999
DOI: 10.1021/jp991373t
|View full text |Cite
|
Sign up to set email alerts
|

Normal Modes for Chemical Reactions from Time Series Analysis

Abstract: A method is presented for probing chemical reaction mechanisms experimentally with perturbations and measurements of the response. Time series analysis and the methods of linear control theory are used to determine the Jacobian matrix of a reaction at a stable stationary state subjected to random perturbations. The method is demonstrated with time series of a model system, and its performance in the presence of noise is examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In addition, we believe that this may have experimental importance when the geometry of the limit cycle is reconstructed from experimental data using either quenching techniques 36 or control theory. 37 The ideas presented here for the Hopf bifurcation have been implemented numerically into a software tool BRANCH 38 which supports bifurcation analysis of dynamical systems described by autonomous ordinary differential equations and discrete iterated maps. For such systems, all ''simple'' codimension-one bifurcations are handled: Saddle-node, transcritical, pitchfork, and Hopf-Neimark-Sacker bifurcations of stationary, periodic, and fixed point solutions, as well as period doubling bifurcations of periodic orbits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we believe that this may have experimental importance when the geometry of the limit cycle is reconstructed from experimental data using either quenching techniques 36 or control theory. 37 The ideas presented here for the Hopf bifurcation have been implemented numerically into a software tool BRANCH 38 which supports bifurcation analysis of dynamical systems described by autonomous ordinary differential equations and discrete iterated maps. For such systems, all ''simple'' codimension-one bifurcations are handled: Saddle-node, transcritical, pitchfork, and Hopf-Neimark-Sacker bifurcations of stationary, periodic, and fixed point solutions, as well as period doubling bifurcations of periodic orbits.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, it is assumed that the identity of the chemical species present in the network is known, and the goal of the structure inference is to identify the species interactions [21] under some pre-imposed dynamics law [30]. This problem is of particular interest in the context of molecular and systems biology under the law of mass action dynamics, and as such has received considerable attention in the literature [3, 10, 14, 15, 17, 27, 31, 32].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of the most recent literature in this area can be found in [2]. One class of network identification approaches is concerned with the determination of Jacobian matrix elements [8], either from time-series analysis or from quenching studies [4]. Jacobian entries reveal interactions between species in the network, and which species do not interact with each other.…”
Section: Introductionmentioning
confidence: 99%